Safety and efficacy of immune checkpoint inhibitors in patients with non-small cell lung cancer and hepatitis B or hepatitis C infection. (July 2020) - Pertejo-Fernandez, Ana; Ricciuti, Biagio; Hammond, Sarah P.; Marty, Francisco M.; Recondo, Gonzalo; Rangachari, Deepa; Costa, Daniel B.; Awad, Mark M.
Highlights: Information about viral hepatitis and NSCLC under ICIs therapy is scarce. In our experience, ICIs appear to be safe, with no high-grade hepatic irAEs. Prospective trials are needed to assess the safety of ICIs in this population. Abstract: Objectives: The safety and efficacy of immunotherapy among patients with history of hepatitis B (HBV) or hepatitis C virus (HCV) infection and non-small cell lung cancer (NSCLC) remains unclear as this population has traditionally been excluded from clinical trials with immune checkpoint inhibitors (ICIs). Materials and methods: We retrospectively evaluated treatment toxicities and clinical outcomes in nineteen patients with NSCLC and history of past or chronic HBV (16 cases, two of these had HCV co-infection) or chronic HCV infection (five cases), who received a programmed death-1 (PD-1) pathway inhibitor. Results: The overall response rate to immunotherapy was 35 %, and the median progression-free survival was 4.5 months. After ICI initiation, increases in liver function tests (LFTs) from baseline were infrequent and mild, and no patients experienced grade 3 or 4 hepatic immune-related adverse events or required ICI discontinuation or corticosteroid administration for management of hepatic toxicity. There were no significant changes in viral load or cases of HBV reactivation or HCV flare while on ICI therapy. Conclusion: In this case series, treatment with immunotherapy in patients with NSCLC and past or chronic viral hepatitis appears to be safe, and responses to ICIs can be durable in this population. Additional studies are needed in larger cohorts of patients to determine the safety of immunotherapy in patients with chronic viral infections.